2017
DOI: 10.1038/srep46606
|View full text |Cite
|
Sign up to set email alerts
|

Structure Shapes Dynamics and Directionality in Diverse Brain Networks: Mathematical Principles and Empirical Confirmation in Three Species

Abstract: Identifying how spatially distributed information becomes integrated in the brain is essential to understanding higher cognitive functions. Previous computational and empirical studies suggest a significant influence of brain network structure on brain network function. However, there have been few analytical approaches to explain the role of network structure in shaping regional activities and directionality patterns. In this study, analytical methods are applied to a coupled oscillator model implemented in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…All parameters for the models were set to simulate alpha oscillations in the brain. Alpha oscillation models have successfully explained empirically observed brain network behaviors such as functional connectivity, traveling waves, and network state transitions based on electroencephalography (EEG) and magnetoencephalography (MEG) [25,26,2937]. Thus, alpha oscillations were analyzed to understand the behaviors of Φ and the criticality at the brain network level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All parameters for the models were set to simulate alpha oscillations in the brain. Alpha oscillation models have successfully explained empirically observed brain network behaviors such as functional connectivity, traveling waves, and network state transitions based on electroencephalography (EEG) and magnetoencephalography (MEG) [25,26,2937]. Thus, alpha oscillations were analyzed to understand the behaviors of Φ and the criticality at the brain network level.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, most studies have focused on scale-free behavior, showing power law distribution of empirically observed variables. It has also been recently proposed that high correlation between functional and structural brain networks [14,23,25,26,45] and a large pair correlation function (PCF) [24,46] is evidence of criticality. In both the brain network model and empirical EEG data, we estimated criticality with PCF, which is the variance of global phase synchronization and is equivalent to susceptibility in statistical physics where Re[ z(t) ] is the real part of the z(t) in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Like mammals, wakeful insect brains also face functional challenges in adjusting fast sensory inputs based on prior experience on a slower time scale (Card and Dickinson, 2008; Combes, 2015; Kim et al, 2015; Mischiati et al, 2015). In addition, recent work suggests that the topological organization of the mammalian brain, which shares a number of similarities with the topological organization of the fly brain (Shih et al, 2015), influences the direction of information flow (Moon et al, 2015; Mejias et al, 2016; Moon et al, 2017). This evidence suggests that similar dynamic characteristics of FF and FB processing will be present in the insect brain.…”
Section: Introductionmentioning
confidence: 99%
“…The = 2 and is an initial angular natural frequency of each ℎ oscillator. We used a Gaussian distribution for natural frequency with a mean frequency of 10 Hz and standard deviation of 0.5 Hz to simulate the alpha bandwidth of human EEG activity [20][21][22]24,51]. We also used the homogeneous coupling term = between the ℎ and ℎ oscillators from 0 to 0.4 with = 0.002, which determines the global connection strength among brain regions.…”
Section: Simulation Of Networked Alpha Oscillations In a Human Brain mentioning
confidence: 99%
“…In this study, we hypothesized that perceptual binding associates with the brain's network response, and the network response largely depends on the ongoing coupled oscillation properties at stimulus onset. Recent studies have revealed that alpha oscillations transfer information through traveling waves in the cortex, and the global functional connectivity of alpha oscillations reflect conscious and unconscious states [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%